Development and evaluation of a regional water poverty index for Benin - Heidecke, Claudia (International Food Policy Research Institute, 2006)
The paper discusses the application of the Water Poverty Index (WPI) as a monitoring tool for Benin’s water sector. Benin is currently in a process of political decentralization shifting responsibility for and administration of rural water supplies from the national to the communal level. Appropriate indicators are needed for monitoring and analyzing the progress of the water sector for each community. The Water Poverty Index allows monitoring of a combination of aspects affecting rural water management, including water sources, access to and use of water, human capacity to manage water, and environmental impacts. The application of this index is tested for Benin at the regional level. A series of variables have been chosen for inclusion into the index following data collection and analysis in Benin under the IMPETUS project. Results show a clear distinction between communes in the north and the south of the country and WPI rankings are similar to those for poverty levels. The paper concludes with a discussion of the strengths and weaknesses of the WPI and suggests improvements for its application at the communal level.